Storability of Puna as Influenced by Sprout Control Method and Stage of Harvested Yam - Amponsah, SK; Rees, D; Abayomi, L; Akowuah, JO; Bortey, HM; Bessah, E; Gyening, K (JOURNAL OF ROOT CROPS, 2017)
Sprout development, which is the break of dormancy period in yams, affects its quality and dry matter quantity as well as its market value. This study assessed the effect of various sprout control methods on puna yam variety at different harvesting stages during storage in both traditional and improved barns. The traditional structure was constructed by local farmers and improved structure by scientists from the CSIR-Crops Research Institute, Kumasi using locally available materials. A total of 160 puna yam tubers were sampled and randomly stocked into both yam structures. Weight, sprouting (number, length and weight of sprouts) and externally visible rot data were taking at stocking and at 30 days’ interval for 120 days’ storage period. Sprout control treatments/methods considered were; control, hand snap, full cut and half cut. Environmental conditions in both structures were conducive for yam storage. However, the traditional storage structure maintained relatively higher moisture resulting in the higher mean monthly relative humidity experienced. Full cut control method had the highest percentage weight loss (51%) and half cut method, the highest sprouting rate and percentage visible rot at 9.2 cm/d and 36% respectively. In terms of yam sprout control, hand snap was best at reducing weight loss, tuber rot and sprout rate. Also, unmilked condition recorded highest percentage weight loss and rot. Therefore, milked condition of puna yam is a better option for minimized weight loss and rot. There was no significant difference (p<0.05) in percentage weight loss and rot for sprout control methods and harvesting stages. However, there was significant difference (p<0.05) in number of sprout and rate of sprout for sprout control method and harvesting stage. Weight loss had a negative relationship with number of sprout, rate of sprout, sprout length and weight whereas percentage visible rot had a good positive correlation with weight loss. It is however recommended that similar study be conducted on other yam varieties under varying storage conditions and ecologies. Again, the effect of yam positioning at storage on sprout control could also be looked at